AdipoRon may be benefit for atherosclerosis prevention - Maryam Esfahani; Nooshin Shabab; Massoud Saidijam (Iranian Journal of Basic Medical Sciences, 2017)
Atherosclerosis has serious role in coronary arteries disease,so it is important to establish effective strategies for prevention or even treatment of atherosclerosis. Adiponectin, as one of the most abundant adipokines, has insulin sensitivity, anti-inflammatory and anti-atherogenic properties. Disturbed adiponectin actions through its receptor, (AdipoR1 and AdipoR2) may be involved in atherosclerosis development. Some adiponectin effects are mediated by AMPK and PPAR-α signaling. AdipoRon is an orally active synthetic molecule which can bind to AdipoR1, Adipo R2 and activate them. AdipoRon can activate AdipoR1-AMPK- PGC-1α pathway and AdipoR2-PPAR-α pathway. Some studies indicated insulin sensitivity, anti-apoptotic and anti-oxidative effect of AdipoRon. We hypothesize that AdipoRon has anti atherosclerotic effect and may suppress atherosclerosis processes. With confirmation the benefit role of AdipoRon on atherosclerosis, it may be used in patients at risk of atherosclerotic development.